A case report on Clostridium baratti in placenta: pathogen or commensal - Arpita Panda; Bhawna Sharma; Nidhi Punia; Dharsshana Shanmugasundaram; Deepthi Nair (International Journal Of Community Medicine And Public Health, 2026)
Clostridium baratti is a rarely reported anaerobic bacterium, primarily isolated from immunocompromised patients. We report a case of C. baratti isolated from placental tissue in a 32-week pre-rupture of membranes patient with acute chorioamnionitis. The mother presented with fever, elevated inflammatory markers (CRP 42 mg/l, WBC 16,500/μl), and fetal tachycardia. Placental culture revealed C. baratti (anaerobic culture) and non-pathogenic organisms (aerobic culture). The neonate developed early-onset sepsis with leukopenia, thrombocytopenia, elevated CRP, and coagulopathy. Neonatal blood culture grew commensals; anaerobic cultures were not obtained on day 0. Four lines of evidence- isolation during active maternal infection, polymicrobial ascending flora, growth in infected tissue, temporal relationship to neonatal sepsis, coverage by empiric metronidazole, and isolation from protected placental tissue, may suggest C. baratti as pathogenic. This case suggests C. baratti as a pathogen in obstetric-neonatal infections and highlights the need for routine anaerobic culture of placental tissue and anaerobic blood cultures from chorioamnionitis-exposed neonates.